Design crash cushion using waste tire for toll plaza barrier - Md Palil, Md Dan; Abdull Mutalib, Fadhli Akmal (Penerbit Universiti Teknikal Malaysia Melaka, 2012)
Nowadays, there are many victims of accidents at toll plazas spread in the daily newspaper. Based on the severed incident, there are many humans died and seriously injured. Thus, accidents at the toll plaza is the main cause of this study. Besides that, one of the factor that cause the accident is the barrier systems such as crash block that made from concrete preferred the safety of the workers where they protect the vulnerable from harm tollbooth violations from the vehicle. This study aimed to design a crash cushion to be placed in front of crash block. In this study, waste tires are used as material crash cushion. The waste tires is used in this study because its can reduced envirnmental pollution and its also can counter the requirements of rubber demand. Moreover, the waste tires has been cut and crushed into fine powder using a Crusher Machine. Then, the waste tires is routed to make the crash cushion. Actually, a main process of producing the crash cushion is injection moulding process. In addition, this process has been studied to get more information about the flow process in producing the crash cushion. Furthermore, samples of prototype will be made to show the real view crash cushion. Other than that, results from the test data will be recorded in order to make this study qualified in the future.